POTENSI HASIL GALUR-GALUR PADI SAWAH GENJAH TAHAN TUNGRO - Rini Ismayanti; Asmary Muis; Ristanti Nuria Laili Isnaini (UIN Sunan Gunung Djati Bandung, 2023)
Tungro disease is an important disease in rice plants that can cause puso. One of the effective efforts to prevent the outbreak of tungro disease is to plant tungro resistant varieties. The tungro-resistant varieties are still limited, while the tungro virus continues to change, so that the resistance of varieties can be broken. Therefore, it is necessary to assemble a new variety. The aim of the study was to determine the yield potential of 10 tungro-resistant early paddy rice lines. The research was conducted at IP2TP Lolittungro in the second planting season in 2021, June to December. The comparison varieties used were Inpari 36 and Inpari 33. The experiment was arranged in a Randomized Block Design (RAK) using 3 replications. The data were tested by analysis of variance with the F test and if they were significantly different, they continued with the LSD test. The yield potential obtained from the comparison varieties Inpari 33 is 6.17 tons/ha and Inpari 36 is 7.97 tons/ha. The results of the analysis showed that 7 (seven) lines were more mature than the comparison. As for the potential yield obtained, there are 2 lines that exceed one of the comparison varieties, namely BP20420b-2-0-2-3-LR-2-1-1 and BP14880e-1-Kn-3-0-LR-1-1-1 with production of 6.36 tons/ha and 6.86 tons/ha, respectively. The two lines were also supported by the highest percentage of filled grain, namely 75.53% and 86.27%.